Application of digital technologies in the Singapore logistics industry. Part B : warehousing sector - Lee, Yiling (Nanyang Technological University, 2020)
Logistics and supply chain are part of our everyday lives, from the food on our table, to the clothes that we are wearing, to the things that we are using. It is very important to all of us. Digitalisation of the logistics sector is one of the key determinants to improve efficiency and accuracy and also increasing safety in the operating processes. It is also vital as the demands of customers and consumers are ever increasing and the only way to cope with these is to be innovative and digitalising the operations. In this research paper, we will be focusing on the application of digital technologies on the Singapore logistics industry in the context of the Warehousing sector. Interviews with industrial professionals and further researches are conducted to further understand the usage of these technologies on the warehouses to evolve them from traditional warehouses into ‘smart’ warehouses, the benefits they will bring as well as the challenges faced especially in Singapore. From our interviews, we understood that digitalisation is a revolution for the logistic sectors and with digitalisation, logistics firms will be able to meet customers’ needs better and will be able to improve their manpower allocation, accuracy with reduction of human errors, efficiency of the operations. The technologies used in logistics firms were identified and analysis was done to further study on the impact that will bring about by those technologies. It is proven in our analysis that digitalisation of warehouses in the logistics sector is essential and will definitely be of great help to all the parties involved in the supply chain. There is some inertia in digitalisation for some logistics firms due to the high initial cost involved in the transformation which can put financial strains on small firms with lesser financial capabilities, but it is important for firms to see the benefits it brings to their operations to achieve accuracy and efficiency.